2004
DOI: 10.1521/scpq.19.4.299.53506
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of School Psychology Faculty by Graduating University.

Abstract: Shortages of school psychologists have been documented for many years with this deficiency extending not just to practitioners but to trainers as well. This article presents the results of a search to identify individuals employed in academic institutions and their graduating universities. Using an Internet search and mailings to doctoral degree-granting school psychology programs, 633 individuals were identified as having graduated from a school psychology program in the United States or Canada and being curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 15 publications
2
26
1
Order By: Relevance
“…Generally, the findings from this survey indicate that, for the most part, the perceptions about workplace climate and experiences of male academic school psychologists parallel those reported by women in a previous study (Akin‐Little et al, 2004). Although differential treatment based on gender was perceived to exist for both genders, it was not of a large‐scale magnitude.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Generally, the findings from this survey indicate that, for the most part, the perceptions about workplace climate and experiences of male academic school psychologists parallel those reported by women in a previous study (Akin‐Little et al, 2004). Although differential treatment based on gender was perceived to exist for both genders, it was not of a large‐scale magnitude.…”
Section: Discussionsupporting
confidence: 80%
“…In 1971, Farling and Hoedt reported that women comprised only 18% of school psychology faculty. This increased to 24% in 1977 (Brown & Lindstrom, 1977), 34% in 1989 (McMaster, Reschly, & Peters, 1989), 46% in 1998 (Thomas, 1998), 51% in 2002 (Curtis, 2002), and 53% in 2004 (Little et al, 2004). Reschly (2000) predicted that women would continue to increase proportionately to men, with women making up 65% of faculty and 50% of program directors by 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2004) conducted the first examination of the research productivity of faculty in APA-accredited school psychology programs using data in the PsycINFO database from 1995 to 1999. Prior to their study, previous research on research in school psychology focused only on articles that were published in the major school psychology journals (e.g., Little, 1997;Little et al, 2004;O'Callaghan, 1974;Reynolds & Clark, 1984;Roberts et al, 2006;Webster et al, 1993). Carper and Williams, however, showed that 70% of the publications by school psychology program faculties appeared in other social and behavioral science journals.…”
Section: Publication Outletsmentioning
confidence: 99%